Adjuvant nivolumab plus ipilimumab versus placebo for localised renal cell carcinoma after nephrectomy (CheckMate 914): a double-blind, randomised, phase 3 trial. Issue 10379 (11th March 2023) - Motzer, Robert J; Russo, Paul; Grünwald, Viktor; Tomita, Yoshihiko; Zurawski, Bogdan; Parikh, Omi; Buti, Sebastiano; Barthélémy, Philippe; Goh, Jeffrey C; Ye, Dingwei; Lingua, Alejo; Lattouf, Jean-Baptiste; et al.
Summary: Background: Effective adjuvant therapy for patients with resected localised renal cell carcinoma represents an unmet need, with surveillance being the standard of care. We report results from part A of a phase 3, randomised trial that aimed to assess the efficacy and safety of adjuvant nivolumab plus ipilimumab versus placebo. Methods: The double-blind, randomised, phase 3 CheckMate 914 trial enrolled patients with localised clear cell renal cell carcinoma who were at high risk of relapse after radical or partial nephrectomy between 4–12 weeks before random assignment. Part A, reported herein, was done in 145 hospitals and cancer centres across 20 countries. Patients were randomly assigned (1:1) to nivolumab (240 mg) intravenously every 2 weeks for 12 doses plus ipilimumab (1 mg/kg) intravenously every 6 weeks for four doses, or matching placebo, via an interactive response technology system. The expected treatment period was 24 weeks, and treatment could be continued until week 36, allowing for treatment delays. Randomisation was stratified by TNM stage and nephrectomy (partial vs radical). The primary endpoint was disease-free survival according to masked independent central review; safety was a secondary endpoint. Disease-free survival was analysed in all randomly assigned patients (intention-to-treat population); exposure, safety, and tolerability were analysed in all patients who received at least one dose of study drug (all-treated population). This study is registered with ClinicalTrials.gov, NCT03138512 . Findings: Between Aug 28, 2017, and March 16, 2021, 816 patients were randomly assigned to receive either adjuvant nivolumab plus ipilimumab (405 patients) or placebo (411 patients). 580 (71%) of 816 patients were male and 236 (29%) patients were female. With a median follow-up of 37·0 months (IQR 31·3–43·7), median disease-free survival was not reached in the nivolumab plus ipilimumab group and was 50·7 months (95% CI 48·1 to not estimable) in the placebo group (hazard ratio 0·92, 95% CI 0·71–1·19; p=0·53). The number of events required for the planned overall survival interim analysis was not reached at the time of the data cutoff, and only 61 events occurred (33 in the nivolumab plus ipilimumab group and 28 in the placebo group). 155 (38%) of 404 patients who received nivolumab plus ipilimumab and 42 (10%) of 407 patients who received placebo had grade 3–5 adverse events. All-cause adverse events of any grade led to discontinuation of nivolumab plus ipilimumab in 129 (32%) of 404 treated patients and of placebo in nine (2%) of 407 treated patients. Four deaths were attributed to treatment with nivolumab plus ipilimumab and no deaths were attributed to treatment with placebo. Interpretation: Adjuvant therapy with nivolumab plus ipilimumab did not improve disease-free survival versus placebo in patients with localised renal cell carcinoma at high risk of recurrence after nephrectomy. Our study results do not support this regimen for the adjuvant treatment of renal cell carcinoma. Funding: Bristol Myers Squibb and Ono Pharmaceutical.